A formação do balé brasileiro e a crítica jornalística: nacionalismo e estilização - Pereira, Roberto Wagner (2002)
This work aims at mapping the elements which were responsible for the idea of a Brazilian ballet taking into consideration both its formation and its thematic aspects. In order to do that, journalistic critics of dance have been elected as its main feature, observing how their especialization was directly connected to the especialization of Brazilian groups Who were anxious to create their ballet. The City of Rio de Janeiro, then the nation's capital, was the stage where the first steps towards the creation of a Brazilian ballet took place still during the first half of the 20th century. This fact coincided with a period in history known as Estado Novo (The New State), which impregnated the construction of this ballet with a sense of ufanistic Brazility, present in the political ideology of that time. Journalistic critics, for their turn, contributed directly to this construction, for they analyzed ballet presentations in the opening seasons from the standpoint of the New State ideology. Therefore, this work has mapped all critiques from major newspapers at the time, and has tried to unravel how the idea of Brazility developed in the dialogue between ballet and the press